Practice Parameter update: Evaluation and management of driving risk in dementia: Report of the Quality Standards Subcommittee of the American Academy of Neurology - Iverson, D.J. (American Academy of Neurology, 2010)
OBJECTIVE: To review the evidence regarding the usefulness of patient demographic characteristics, driving history, and cognitive testing in predicting driving capability among patients with dementia and to determine the efficacy of driving risk reduction strategies. METHODS: Systematic review of the literature using the American Academy of Neurology's evidence-based methods. RECOMMENDATIONS: For patients with dementia, consider the following characteristics useful for identifying patients at increased risk for unsafe driving: the Clinical Dementia Rating scale (Level A), a caregiver's rating of a patient's driving ability as marginal or unsafe (Level B), a history of crashes or traffic citations (Level C), reduced driving mileage or self-reported situational avoidance (Level C), Mini-Mental State Examination scores of 24 or less (Level C), and aggressive or impulsive personality characteristics (Level C). Consider the following characteristics not useful for identifying patients at increased risk for unsafe driving: a patient's self-rating of safe driving ability (Level A) and lack of situational avoidance (Level C). There is insufficient evidence to support or refute the benefit of neuropsychological testing, after controlling for the presence and severity of dementia, or interventional strategies for drivers with dementia (Level U). GLOSSARY: AAN: = American Academy of Neurology; AD: = Alzheimer disease; CDR: = Clinical Dementia Rating; CI: = confidence interval; MMSE: = Mini-Mental State Examination; OR: = odds ratio; ORDT: = on-road driving test; QSS: = Quality Standards Subcommittee; RR: = relative risk.